ABON IKAN BETUTU (Oxyeleotris marmorata) YANG DISUBSTITUSI DENGAN BUAH NANAS MADU (Ananas comosus L. Meer) - Yusra; Nadya, Dhifa Khairi (Fisheries Product Technology Department, Faculty of Marine Science and Fisheries, Universitas Maritim Raja Ali Haji, 2024)
MARINADE Vol. 07(02) : 1 – 5 (Oktober 2024)e-ISSN : 2654-4415online : http://ojs.umrah.ac.id/index.php/marinade1ABON IKAN BETUTU (Oxyeleotris marmorata) YANG DISUBSTITUSI DENGANBUAH NANAS MADU (Ananas comosus L. Meer)Difa Khairi Nadya1), dan Yusra1*)1)Program Studi Pemanfaatan Sumberdaya Perikanan, Fakultas Perikanan dan IlmuKelautan, Universitas Bung Hatta, Padang, 25133, Indonesia.*korespondensi: yusra@bunghatta.ac.idABSTRACTFish floss is a product made from shredded fish meat combined with specific seasonings,processed, through boiling, frying and pressing. The research was conducted in May 2024 at the FishProcessing Laboratory of the Faculty of Fisheries and Marine sciences at bung hatta university andVahana Scientific Laboratory. The aim of this study is to analyze the effect of adding honey pineapple(Ananas comosus L.Meer) fiber on the proximate and organoleptic quality of betutu fish floss(Oxyeleotris marmorata). The method used is experimental. The treatment applied is (A) betutu fishfloss (Oxyeleotris marmorata) without the addition of honey pineapple fiber (Ananas comosus L.Meer)and (B) betutu fish floss (Oxyeleotris marmorata) with the addition of honey pineapple fiber (Ananascomosus L.Meer). the data obtained were analyzed using a two-sample test (T-test). The results showthat the addition of honey pineapple fiber affects the organoleptic and proximate quality of betutu fishfloss.